A Comparative Study of Slum Area Management in South Korea, Colombia, India, and Indonesia - Fani Hendra Saputra; Alfitri Alfitri; Andries Lionardo; Abdul Nadjib (Universitas KH. Abdul Chalim Mojokerto, 2025)
The prevalence of slums remains a pressing global issue, with more than 1.1 billion people currently living in such conditions. This situation reflects persistent inequalities in access to adequate housing and basic services. To address this challenge, cross-country learning is essential to identify and adapt best practices for sustainable slum upgrading. This study employed qualitative methods to examine slum upgrading initiatives in South Korea, Colombia, India, and Indonesia. Data were collected through document analysis, literature review, and case study approaches. The findings indicate that the success of slum upgrading is determined not only by physical improvements but also by the quality of multi-stakeholder collaboration, community leadership, and consistent policy implementation. The cases of South Korea and Colombia highlight the importance of social mobilization and inclusive planning, whereas the cases of India and Indonesia underscore ongoing challenges related to coordination and funding constraints. This study underscores the need to strengthen local government capacity, enhance community participation, and develop multi-source financing schemes as key prerequisites for inclusive, empowered, and sustainable slum transformation. The cross-country insights presented here provide valuable policy lessons that can be adapted to improve slum upgrading practices in Indonesia.